The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.33882
|View full text |Cite
|
Sign up to set email alerts
|

Complications During Hospitalization in Patients With SARS-CoV-2 Pneumonia in a Romanian Pulmonary Center

Abstract: The coronavirus disease (COVID-19) was declared a pandemic by the World Health Organization (WHO) on March 11, 2020. Facing a new and unknown virus, the entire medical community made considerable efforts to find a specific treatment, develop guidelines, and even create a vaccine. Besides all the measures taken, a wide range of complications associated with the disease increased the mortality and morbidity rates, adding more difficulty to the management of the patients. Study designWe performed a retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…The study by Davidescu et al observed a statistically significant difference between elders and non-elders in regard to AST [ 62 ]. Other cases were reported with elevated levels as well, with a tendency towards elevated AST rather than a modified ALT [ 23 , 24 , 25 , 26 , 30 , 34 , 35 , 36 , 37 , 59 , 64 , 79 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Davidescu et al observed a statistically significant difference between elders and non-elders in regard to AST [ 62 ]. Other cases were reported with elevated levels as well, with a tendency towards elevated AST rather than a modified ALT [ 23 , 24 , 25 , 26 , 30 , 34 , 35 , 36 , 37 , 59 , 64 , 79 , 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is a retrospective observational study described before in an article where we analyzed complications in hospitalized patients with SARS-CoV-2 pneumonia [ 7 ]. This study was approved by the Marius Nasta Institute of Pneumology Ethics Committee and all the patients signed the informed consent during hospital admission.…”
Section: Methodsmentioning
confidence: 99%
“…This is a retrospective observational study described before in an article where we analyzed complications in hospitalized patients with SARS-CoV-2 pneumonia [7]. This study was approved by the Marius Nasta The diagnosis of pneumothorax or pneumomediastinum was confirmed by chest radiography or chest computed tomography (CT), or by clinical examinations associated with symptoms, with an increase in the severity of symptoms, a drop in oxygen saturation, and the clinical evidence of subcutaneous emphysema.…”
Section: Methodsmentioning
confidence: 99%
“…(13) Como mecanismos de asistencia para encontrar beneficios con pacientes post COVID, la oxigenoterapia hiperbárica es uno de ellos, la cual mostró una mejor funcionalidad a nivel de fuerza, resistencia y mayor calidad de vida, a su vez mejora los parámetros respiratorios y de acidosis metabólica, (14) es por ello que un tratamiento adecuado, puede generar beneficios a nivel metabólico, y reducir las diferentes situaciones que se presentan durante la enfermedad, esto al ser suministrado por vía intravenosa NAD+, como medio terapéutico y dar un manejo apropiado a los síntomas del síndrome postagudo del COVID-19. (15) Es importante destacar que, los pacientes con infección por SARS-CoV-2, que han estado hospitalizados con neumonía, generan dificultades en cualquier parte del organismo, dentro de las cuales se encuentra, la insuficiencia respiratoria (71,14%), hiperglucemia (43,54%), lesión renal (42,67%) o eventos cardiovasculares (7,10%), de esta manera, se ha convertido en un problema clínico, debido a las dificultades que se generan al tratar de forma eficiente estos pacientes, (16) por ello, los sobrevivientes que presentaban complicaciones respiratorias previas al COVID-19 como neumonía, son actualmente una de las poblaciones de riesgo elevado a los síntomas del COVID largo, y, se requiere la evaluación en futuras investigaciones del COVID largo con respecto al equilibrio ácido-base.…”
Section: Estimado Directorunclassified
“…Es importante destacar que, los pacientes con infección por SARS-CoV-2, que han estado hospitalizados con neumonía, generan dificultades en cualquier parte del organismo, dentro de las cuales se encuentra, la insuficiencia respiratoria (71,14%), hiperglucemia (43,54%), lesión renal (42,67%) o eventos cardiovasculares (7,10%), de esta manera, se ha convertido en un problema clínico, debido a las dificultades que se generan al tratar de forma eficiente estos pacientes, 16 por ello, los sobrevivientes que presentaban complicaciones respiratorias previas al COVID-19 como neumonía, son actualmente una de las poblaciones de riesgo elevado a los síntomas del COVID largo, y, se requiere la evaluación en futuras investigaciones del COVID largo con respecto al equilibrio ácido-base.…”
unclassified